FOOD PACKAGING : innovations and shelf-life - Cruz, Rui M. S. (CRC Press, 2020)
Food Packaging: Innovations and Shelf-life covers recently investigated developments in food packaging and their influence in food quality preservation, shelf-life extension, and simulation techniques. Additionally, the book discusses the environmental impact and sustainable solutions of food packaging. This book is divided into seven chapters, written by worldwide experts. The book is an ideal reference source for university students, food engineers and researchers from R & D laboratories working in the area of food science and technology. Professionals from institutions related to food packaging.